Elvira García y García: paratexts and Peruvian intellectuality (1896-1948) - Gonzales Lucana, Alejandra (2025)
This article analyzes how the paratexts in the work of the Peruvian educator Elvira García y García allow us to know the relationships she established with the intellectuals in Peru from 1896 to 1948. From the paratextual analysis, we can establish that the connection of the educator with institutions and personalities was active and notable, which allowed her to strengthen her role as a woman in the field of education, culture, social assistance and child protection.